Significance of the concept of quality of education for didactics of mathematics in universities in Poland - Maciuk, Arkadiusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
In the last twenty years the number of students and universities in Poland has increased more than four times. This quantitative increase has meant for the didactics of mathematics the need to reduce the level of education. Currently, this upward trend is in reverse and the higher education sector, practically in all Europe, can expect reductions. The current efforts of policy makers and academic staff are focused on improving the quality of education in order – among other reasons – to stay competitive. Shifting focus from quantity and efficiency to quality of education can be an opportunity but also a threat. The problem is how to understand the quality of education and how it can be put into pedagogical practice. Maths education has its own specific conditions. Taking them into account may result not only in improving the quality of didactics of mathematics, but more widely – improving the quality of what is understood as the process of higher education. The article gives an overview of the changes taking place in the Polish higher education sector over the last two decades and of the various definitions of the quality of education. It also presents some conclusions on the relation between the interpretation of the quality of education and didactics of mathematics.
Didactics of Mathematics, 2013, Nr 10 (14), s. 65-76
Keywords: didactics of mathematics; quality of education; higher education sector in Poland